Pemanfaatan Buah Lerak Sebagai Bahan Utama dalam Pembuatan Sabun Cair Ramah Lingkungan di Pekon Kubu Perahu Lampung Barat - Sisdianto, Ersi; Hening, Jeni Latri; Marsilawati, Devi; Al Darda, Fakitha; Larasati, Nurfadila Dewi; Rizki, Aprilia; Nalisa, Rika; Asmara, Mahesa Dwi; Maghfi, Muhammad (Abdimas Indonesian Journal, 2024)
Soapnuts or commonly called soapnuts are plants with seeds used in traditional detergents, consisting of 75% flesh and 25% seeds. The advantage of this plant is that it can be used as a raw material for making detergent. The method used in this community service activity is in collaboration with the PKK group in Pekon Kubu Perahu, Balik Bukit District, West Lampung Regency, which consists of 20 members. This activity is a socialization about the dangers of conventional soap, the active compound content of soapnuts, training in manufacturing techniques and the production process of processing soapnuts into liquid soap. The result of this service is the processing of soapnuts into liquid laundry soap, providing a positive impact on PKK mothers in Pekon Kubu Perahu, namely they can make their own environmentally friendly and safe laundry soap. Soapnuts are plants that contain chemical compounds with bioactivity as antibacterials. The conclusion of this service activity is that through socialization and direct practice, PKK mothers can learn the benefits of using soapnuts in making economical and environmentally friendly liquid laundry soap.